Medicinal and pesticidal potentials of the constituents of the essential oil from Adenia cissampeloides leaves - Ogunlesi, Modupe (Array, 2019)
Adenia cissampeloides (Planch. ex Hook.) Harms is used in alternative medicine primarily for the management of hypertension and several other diseases. Isolation and GC-MS analysis of five essential oils collected fractionally and over 4 h by hydrodistillation from the dried leaves were carried out. The constituents included phytol, α-linolenic acid, n-hexadecanoic acid, hexahydrofarnesyl acetone, (13S)-8,13-epoxy-labd-14-ene, kaur-16-ene, guaiol, α-gurjunene, and α-elemene. Several bioactivities of the constituents as well as their potential applications in medicine and the pharmaceutical and pesticidal industries are discussed. Essential oils from some other plants have several constituents in common with those isolated from A. cissampeloides. The bioactivities of such plants are used to suggest other possible applications of A. cissampeloides.